A highly sensitive SERS-based platform for Zn(ii) detection in cellular media. Issue 11 (16th January 2017) - Zhuang, Hongjun; Wang, Zhenzhen; Zhang, Xiangchun; Hutchison, James A.; Zhu, Wenfeng; Yao, Zhiyi; Zhao, Yuliang; Li, Min
Abstract : HBA SERS peak frequency shifts in response to coordination are used to analyze the concentration of Zn(ii ) with ultra-high sensitivity. Abstract : We report a highly sensitive and selective surface-enhanced Raman scattering (SERS)-based detection of aqueous Zn(ii ) ions (limit of detection 10 −14 M). Spectral changes for a silver nanoparticle-bound Raman reporter upon Zn(ii ) chelation constitutes the assay, which is applied to drinking water and to measurements of cellular uptake of Zn(ii ).